Antimicrobial resistance among invasive Haemophilus influenzae strains: results of a Brazilian study carried out from 1996 through 2000 - Casagrande,S.T. (2002)
A total of 1712 strains of Haemophilus influenzae isolated from patients with invasive diseases were obtained from ten Brazilian states from 1996 to 2000. ß-Lactamase production was assessed and the minimum inhibitory concentrations (MIC) of ampicillin, chloramphenicol, ceftriaxone and rifampin were determined using a method for broth microdilution of Haemophilus test medium. The prevalence of strains producing ß-lactamase ranged from 6.6 to 57.7%, with an overall prevalence of 18.4%. High frequency of ß-lactamase-mediated ampicillin resistance was observed in Distrito Federal (25%), São Paulo (21.7%) and Paraná (18.5%). Of the 1712 strains analyzed, none was ß-lactamase negative, ampicillin resistant. A total of 16.8% of the strains were resistant to chloramphenicol, and 13.8% of these also presented resistance to ampicillin, and only 3.0% were resistant to chloramphenicol alone. All strains were susceptible to ceftriaxone and rifampin and the MIC90 were 0.015 µg/ml and 0.25 µg/ml, respectively. Ceftriaxone is the drug of choice for empirical treatment of bacterial meningitis in pediatric patients who have not been screened for drug susceptibility. The emergence of drug resistance is a serious challenge for the management of invasive H. influenzae disease, which emphasizes the fundamental role of laboratory-based surveillance for antimicrobial resistance.